(untitled) (Annals of Medical Research, 2021)
Aim: Neutrophil-to-lymphocyte ratio (NLR) is a marker of systemic inflammation that correlates with coronary artery disease. The Syntax score is an angiographic tool used in grading the complexity of coronary artery disease (CAD). The aim of this study is that NLR is associated with a greater CAD complexity in patients with stable angina pectoris with chronic total occlusion.Materials and Methods: A total of 495 patients who underwent coronary angiography and who had stable angina pectoris with chronic total occlusion in at least 1 vessel were included in the study. The syntax score was used to determine coronary complexity.Results: Patients with CAD were evaluated by grouping according to 2 different criteria as pointed in the European Society of Cardiology (ESC) revascularization guide. When the syntax S is divided into 3 groups (Syntax score 1-22, 23-32,> 32) according to their score values, or 2 groups (Syntax score 1-21 and> 22 or 1-31 and> 31) according to their Syntax score values, NLR was higher in high Syntax score groups than in low groups (p 32) or 2 groups according to Syntax score values (Syntax score 1-21 and >22 or 1-31 and >31) as pointed in ESC revascularization guideline, high Syntax score group having a higher NLR than low group (p0.05). However, when the patients were divided into 3 groups according to the Syntax score, it was seen that there was no statistical difference in terms of NLR values between the high group and the middle group or the middle group and the low group of the Syntax score.Conclusion: In this study, it has been demonstrated that NLR can be used for the determination of the complexity of the disease in patients with stable angina pectoris with chronic total occlusion. However, in determining the degree of complexity in the patients with stable angina, discrimination of the patients close to each other may not be sufficient.